Dose–response relationship between hand-transmitted vibration and hand-arm vibration syndrome in a tropical environment. Issue 7 (5th May 2013) - Su, Anselm Ting; Maeda, Setsuo; Fukumoto, Jin; Darus, Azlan; Hoe, Victor C W; Miyai, Nobuyuki; Isahak, Marzuki; Takemura, Shigeki; Bulgiba, Awang; Yoshimasu, Kouichi; Miyashita, Kazuhisa
Abstract : Objectives: The dose–response relationship for hand-transmitted vibration has been investigated extensively in temperate environments. Since the clinical features of hand-arm vibration syndrome (HAVS) differ between the temperate and tropical environment, we conducted this study to investigate the dose–response relationship of HAVS in a tropical environment. Methods: A total of 173 male construction, forestry and automobile manufacturing plant workers in Malaysia were recruited into this study between August 2011 and 2012. The participants were interviewed for history of vibration exposure and HAVS symptoms, followed by hand functions evaluation and vibration measurement. Three types of vibration doses—lifetime vibration dose (LVD), total operating time (TOT) and cumulative exposure index (CEI)—were calculated and its log values were regressed against the symptoms of HAVS. The correlation between each vibration exposure dose and the hand function evaluation results was obtained. Results: The adjusted prevalence ratio for finger tingling and numbness was 3.34 (95% CI 1.27 to 8.98) for subjects with lnLVD≥20 ln m 2  s −4 against those <16 ln m 2  s −4 . Similar dose–response pattern was found for CEI but not for TOT. No subject reported white finger. The prevalence of finger coldness did not increase with any of the vibration doses. Vibrotactile perception thresholds correlated moderately with lnLVD and lnCEI. Conclusions: The dose–response relationship of HAVS in a tropical environment is valid for finger tingling and numbness. The LVD and CEI are more useful than TOT when evaluating the dose–response pattern of a heterogeneous group of vibratory tools workers.